Interprofessional Collaboration Training: Maternal-Perinatal Care Simulation to Prevent Maternal Mortality Due to Non-Obstetric Pathology (Non-Communicable Diseases) in Bawean Island, Gresik Regency - Sudaryanti, Lestari; Muhalla, Hafna Ilmy; Sulistyorini, Nilly (Journal of Posthumanism, 2025)
Background: Maternal mortality due to non-obstetric pathologies (non-communicable diseases) such as hypertension, diabetes, and cardiovascular disease is a serious challenge in maternal perinatal health, especially in remote areas such as Bawean Island, Gresik Regency. The lack of interprofessional collaboration in managing these cases exacerbates the situation. Interprofessional collaboration training is designed to improve the ability of health workers to provide comprehensive and coordinated care. Objective: This study aims to improve health workers’ understanding and skills in interprofessional collaboration through simulation of maternal perinatal care, particularly in preventing maternal deaths due to non-obstetric pathology. Method: This training involved health workers from various professions (doctors, midwives, nurses, and nutritionists) on Bawean Island. The method used was maternal perinatal case simulation with an interprofessional collaboration approach. Participants were divided into multidisciplinary teams to handle simulated cases that included risk identification, emergency management, and advanced care planning. Evaluation was conducted through pre-test and post-test to measure knowledge improvement as well as direct observation of collaboration skills. Result: The results of the training showed significant improvement in participants’ knowledge and skills regarding the management of non-obstetric pathology in pregnant women. Participants also reported improved interprofessional communication and coordination skills. The simulation successfully identified critical steps in the management of complex maternal perinatal cases. Implication: This interprofessional collaboration training has important implications in improving the quality of maternal perinatal care, particularly in remote areas. This approach can be adopted as a sustainable training model to reduce maternal mortality from non-obstetric pathologies. Policy recommendations include the integration of similar training in health worker education and training programmes at the national level.